African urban harvest agriculture in the cities of Cameroon, Kenya and Uganda - Prain, Gordon; Lee-Smith, Diana; Karanja, Nancy (Springer, 2010)
"In this book, leading specialists in the fields of urban agriculture and urban environment present a unique collection of case studies that examines the growing role of local food production in urban livelihoods in sub-Saharan Africa."--Provided by publisher.